(untitled) (Research, Society and Development, 2022)
Arsenic (As) is considered an environmental contaminant and can be found in water, soil, air and food. The origin of arsenic can be natural or anthropic. The natural sources of this element are minerals, rocks, soils and sediments that contain arsenic in their composition; Anthropogenic sources come from agriculture, considering the improper use of pesticides, herbicides, waste from certain mining activities, refining of non-ferrous metals, in addition to the burning of mineral coal. In Minas Gerais, an important source of arsenic contamination is mining activities. Among the negative impacts, great concern is precisely related to arsenic, which is highly toxic and is present in human supply waters and soils in Minas Gerais. This work aims at the inventory and mapping of the areas impacted by the contamination of soils and groundwater by arsenic. All research was carried out from data obtained from state environmental agencies and elaboration of maps representing contamination in the state. The largest arsenic contaminations are found in the Quadrilátero Ferrífero region and in the municipality of Paracatu, places highlighted by the mining of iron and gold. The arsenic concentrations reported in the consulted studies in the water ranged from 0.1 to 2,980 μg.L-1, while in the soils and sediments, the values ranged from 0.14 mg.kg-1 to 37 mg.kg-1. Knowing the presence, sources, exposure routes, health risks from ingestion and contact with arsenic is extremely important.